THE WEREWOLF IN LATGALIAN FOLKLORE - Skrivļa-Čevere, Jana (Via Latgalica, 2008)
Latgale is the essentially most different and most peculiar Latvian region from the perspectives of language and culture and their interaction with the cultures of other nations. Hence, this article attempts to reveal how the images of werewolves in Latgalian folklore and the means of their expression used in traditional tales differ from the rest territory of Latvia. The aim of the article is to understand the use of this relatively little studied mythical image and the features of their characters in Latgalian folklore. Previously, the author studied the features of werewolf depictions in Latvian folklore in general, and also compared it to Lithuanian folklore. The main source used in the research are five tales of werewolves, which can be found in an electronic version of Pēteris Šmits’ collected fairy tales and tales on http://valoda.ailab.lv/folklora/pasakas/saturs.htm, recorded in the dialect of the Eastern part of Latvia. Different dictionaries and encyclopedias, for example the „Interpretative Dictionary of the Latvian Language” („Latviešu valodas skaidrojošā vārdnīca”) (http://www.ailab.lv/Vardnica/), the „Dictionary of Latvian Etymology” (“Latviešu etimoloģijas vārdnīca”), the „Encyclopedia of Mythology” (“Mitoloģijas enciklopēdija”), and the „Dictionary of Foreign Words” (“Svešvārdu vārdnīca”) were used to describe the symbolical and etymological meaning of a werewolf image. The main methods used in the paper are semiotic and comparative. The semiotic method is used to explain the symbolical meaning of the werewolf image and the semantics of the word. The comparative method is used to compare the comprehension and interpretation of the werewolf image in the tales written in the Latvian and Latgalian languages, as well as to compare the structure of these tales and the use of artistic means of expression. As the result of the research, it is possible to conclude that the Latgalian tales of werewolves show features that both agree with and differ from tales of other regions. However, the means of expression in the Latgalian tales of werewolves are rather different from texts written in other regions. One of the major differences is the language which the tales are written in, as well as emotionally expressive elements in the colloquial speech of the narrators, such as the lexis of the region, dialectisms, similes, hyperbolization, and russicisms.Just like in the majority of tales from other regions, special introduction and conclusion formulas are used. The introduction formula takes the listeners into the world of fairy tales and magic, and the conclusion fromula brings them back into reality. In addition, the use of particular toponyms to gain the effect of credibility is quite common. The motive of shapeshifting wedding guests in a number of Latgalian tales is more characteristic and more common in Lithuanian folklore, but not in the folklore of other Latvian regions. Only in one of the analyzed tales a person turns into a werewolf of his own free will. What’s more, he is not a Latgalian, which subtextually implies dislike and prejudices against an alien, which is relatively typical of Latgalian folklore in general. Also, a special shapeshifting formula – a curse – is found in one tale only. Few techniques are mentioned for retrieving human form – jumping over another shot werewolf’s skin, eating a piece of bread given by a human, or cross-cutting a wolf’s skin. Among these methods the bread technique is the most common also in the tales from other Latvian regions. Also, it should be noted that the word „werewolf” is mentioned in one tale only and an expressive description of a werewolf’s appearance is missing. This probably means that this character was not very popular in Latgalian folklore, which is also proved by the small quantity of these texts. Only one tale is narrated by a man, whereas male narrators are predominant in the other regions. In addition, in some Latgalian tales there are relatively distinguished features of patriarchy, relationships between the rich and the poor, and a peculiar sense of humor for this region and its means of expression. Having conducted the research of the tales of werewolves it is quite safe to assert that the narrator’s place of residence and the region that he/she comes from has a relatively essential meaning in the choice of folkloristic motives. The social and cultural environment, the language, and mutual relations are those preconditions that form a person’s weltanschauung, perception of life and basic values. With their special mentality, emotionally colorful means of expression and an exciting, different language, the Latgalian tales are for sure distinctive from the other ones and are very important for Baltic folklore in general.